IMPROVING AL-QUR'AN AND HADITH LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF THE ACTIVE KNOWLEDGE SHARING STRATEGY AT MAN SOLOK CITY - Pebriyan; Dipalpa Rego; Khadijah (As-Sulthan Journal of Education, 2026)
This study aims to analyze the improvement of students' learning outcomes through the implementation of the Active Knowledge Sharing strategy in the Al-Qur'an Hadith subject at MAN Kota Solok. The study employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The research involved two classes consisting of an experimental class and a control class, each comprising 30 students. Data were collected through learning outcome tests and analyzed using descriptive statistics and the Independent Sample t-Test. The findings revealed that the experimental class achieved a higher posttest mean score (85.53) than the control class (76.87). The mean increase in the experimental class was also greater (19.93 points) compared to the control class (11.67 points). Furthermore, the hypothesis testing showed a significance value of 0.000 (<0.05), indicating a significant difference in learning outcomes between the two groups. The study concludes that the Active Knowledge Sharing strategy is effective in improving students' learning outcomes and can be used as an innovative and collaborative learning strategy in Al-Qur'an Hadith learning at the madrasah level.